SALL4 promotes gastric cancer progression via hexokinase II mediated glycolysis - Shao, Meng (Cancer Cell Int, 2020)
BACKGROUND: The stem cell factor SALL4 is reactivated in human cancers. SALL4 plays diverse roles in tumor growth, metastasis, and drug resistance, but its role in tumor metabolism has not been well characterized. METHODS: The glycolytic levels of gastric cancer cells were detected by glucose uptake, lactate production, lactate dehydrogenase activity, ATP level, and hexokinase activity. QRT-PCR and western blot were used to detect the changes in the expression of glycolytic genes and proteins. The downstream target genes of SALL4 were identified by microarray. The regulation of hexokinase II (HK-2) by SALL4 was analyzed by luciferase reporter assay and chromatin immunoprecipitation assay. Transwell migration assay, matrigel invasion assay, cell counting assay and colony formation assay were used to study the roles of HK-2 regulation by SALL4 in gastric cancer cells in vitro. The effects of SALL4 on glycolysis and gastric cancer progression in vivo were determined by subcutaneous xenograft and peritoneal metastasis tumor models in nude mice. RESULTS: SALL4 knockdown inhibited glucose uptake, lactate production, lactate dehydrogenase activity, ATP level and hexokinase activity in gastric cancer cells, and decreased the expression of glycolytic genes and proteins. Microarray analysis showed that SALL4 knockdown affected glycolysis-related pathway. The regulation of HK-2 gene expression by SALL4 was confirmed by luciferase reporter assay and chromatin immunoprecipitation assay. HK-2 knockdown abrogated the promotion of glycolysis by SALL4 in gastric cancer cells, indicating that HK-2 acts as a downstream effector of SALL4. Moreover, HK-2 knockdown reversed the promoting role of SALL4 in gastric cancer cell proliferation, migration and invasion, suggesting that SALL4 drives gastric cancer progression by upregulating HK-2. CONCLUSIONS: SALL4 promotes gastric cancer progression through HK-2-mediated glycolysis, which reveals a new mechanism for the oncogenic roles of SALL4 in cancer.